Το Ρόδι: το περιοδικό για παιδιά (1977-1982):Είδη και θεματολογία των κειμένων - Παναγιωτίδου, Δ.-Α.; Ευαγγελία Γαλανάκη; Μαλαφάντης, Κωνσταντίνος Δ. (Παιδαγωγική Επιθεώρηση, 2024)
The Pomegranate: the magazine for children (To Rodi: to periodiko gia paidia) was a highly popular Greek children’s magazine that was in circulation during the last two decades of the 20th century and still holds a prominent position in Greek children’s literature. In this paper, we attempted to index and classify the literary and non-literary texts that were included in this magazine during its first edition, from December 1977 to December 1982. The analysis of these texts highlighted the wide range of literary genres that were included in the magazine, as well as the wide range of topics they covered. The texts were classified into 22 thematic categories, among which those appearing with the highest frequency were the following: “History and homeland”, “Books and magazines”, “Child and child experiences”, “Environment and ecology”, and “Ethics and virtues”. The relevance of these thematic categories to the aims of the magazine, to the developmental needs of young readers and to the Greek historical context of the late 20th century is also discussed. The magazine made a significant contribution, both quantitatively and qualitatively, in Greek children’s literature. Through this magazine, remarkable literary works came to the fore. The magazine undoubtedly enhanced children’s and adolescents’ love of reading and promoted the development of their identity as readers.